Pilgrimages on the Portuguese Way to Santiago de Compostela: Evolution and Motivations - Silva, Maria de Fátima Matos da (Religions, 2023)
This research paper is based on the study of the evolution of pilgrimages on the Santiago Way, highlighting the Portuguese Way to Santiago—Central Portuguese Way and Coastal Portuguese Way—which has experienced massive popularity over the years. The primary objective of this work is to develop a comprehensive understanding of the pilgrims’ motivations to undertake the Santiago Way pilgrimage. A mixed methods approach is adopted based on the simultaneous use of quantitative and qualitative data. So, an analysis of secondary data, provided by the Oficina del Peregrino de la Catedral de Santiago de Compostela and by the Municipal Department of Cultural Heritage Management of Porto is combined with a thematic analysis of seven interviews with stakeholders of the Portuguese Way to Santiago. The findings suggest that there is an increase in cultural and sports motivations, although spiritual and religious motivations continue to have a strong presence. The ecumenical character of the Santiago Way is also proved, given the large number of pilgrims of religions other than the Catholic one, who travel these paths—the vast territories that are traversed—until reaching the Cathedral of Santiago de Compostela. A new paradigm still needs to be registered, perceptible in the rise of Turigrims, pilgrims who benefit from support services that mitigate the hardships of the way.